Agama dan Budaya: Konstruksi Imajinatif atau Faktual (Analisis Teks Azimat Aceh) - Ahsana AS, Chairunnisa (Al-Ijtima`i: International Journal of Government and Social Science, 2017)
The past is often considered the temptation as well as the footing that remains to be found traces up to now through manuscripts with hundreds or even millions of texts of cunning works in the past, one of the azimic texts and a cultural heritage that emerged as a representation of the result of direct dialect between culture and religion. Textual actualization becomes important in order to reconstruct the paradigm of past societies about the mythical view which is based on the interculture. Aceh through its azimuth mirrors' heroism and patriotism as well as the etiology of personality and naturalistic diseases, irrespective of the dualism of view between the factual and the irrational.